Effects of immune synergist of Chinese medicinal herbs on the efficacy of vaccination against classic swine fever - Fuchuan Wang; Yibo Yan; Yuhuan Zhang1; Yichao Han; Chao Guan (African Journal of Pig Farming, 2014)
Two-month-old piglets were fed with 1, 1.5 and 2% immune synergist of Chinese medicinal herbs together with vaccination against classic swine fever. Serum IgG and IgM levels increased more than the control group on day 30 (P<0.05). B and T lymphocyte proliferation in piglets fed with 1.5 and 2% herbal immune synergist markedly increased on day 30 as compared to the control group (P<0.05). Improvement was also observed in T lymphocyte CD3+, CD4+, CD8+ and CD3+/CD8+ levels. Meanwhile, there were significant differences in SOD activities and rate of neutrophil phagocytosis between synergist groups and the control group. These results suggest that herbal immune synergist of Chinese traditional herbs prescription enhances the protective effect of classic swine fever vaccine.